Integrated farming system for economic resilience, food security and employment generation for smallholders in western Uttar Pradesh - KAMLESH KUMAR; R P MISHRA; P C GHASAL; JAIRAM CHOUDHARY; A L MEENA; PEYUSH PUNIA; SURESH MALIK; CHANDRA BHANU; NIRMAL; RAGHUVEER SINGH; RAGHAVENDRA K J; MOHD ARIF; et al. (The Indian Journal of Agricultural Sciences)
The sugarcane (Saccharum officinarum L.)-wheat (Triticum aestivum L.) cropping system has caused significant challenges, including groundwater depletion and soil degradation, necessitating the adoption of Integrated Farming Systems (IFS) for diversification and sustainability. The study was carried out during 2021–2024 at ICAR-Indian Institute of Farming Systems Research, Modipuram, Meerut, Uttar Pradesh to evaluate an IFS model designed for small and marginal farmers. Spanning 1.38 ha, the model integrates crops, dairy, horticulture, aquaculture, mushroom cultivation, and boundary plantations, emphasizing resource recycling and economic viability. The model demonstrated a high sugarcane equivalent yield (264.1 t/year), with contributions from crops (43%), dairy (29%), horticulture (15%), and fisheries (7%), achieving net annual returns of ₹5,50,090 and a benefit-cost ratio of 3.42. The model also generated 34% higher man-days (774) of annual employment, reducing seasonal unemployment. Components like fisheries, mushroom cultivation, and boundary plantations contributed significantly to income and ecological sustainability. The IFS approach enhanced food and nutritional security by fulfilling household needs and producing marketable surpluses of cereals, fruits, milk, fish, and mushrooms with a marketable surpluses of cereals (92.8%), fruits (94.6%), and milk (93.7%). This comprehensive system offers a sustainable solution to monocropping issues, boosting income and resilience for farm households.